Exploring Canadian women`s coaching journeys to high-performance sport through composite creative non-fiction - Kramers, S.; Bean, C.; Hummell, C.; Harlow, M. (Qualitative Research in Sport, Exercise and Health, 2025)
While more women are involved in sport through leadership roles, numerous barriers continue to impede women`s sustained occupation of coaching positions in high-performance sport. Sharing women`s stories of barriers and facilitators across their coaching journeys can enhance research, practice and retention of women in meaningful coaching roles. The purpose of this study was to explore Canadian women sport coaches` journeys in high-performance sport, using creative non-fiction. Through individual and focus group interviews, 11 women with diverse coaching backgrounds shared their coaching journeys leading to the 2022 Summer Canada Games, the largest amateur multi-sport event in Canada. Three composite vignettes were crafted to vividly portray the participants` shared experiences of entering and sustaining coaching roles in high-performance sport, navigating challenges as being a mother and coach, forging a better path for the succeeding generation of women coaches, and depending on a supportive community in their journeys. Recommendations are offered to help promote, support and retain women in high-performance coaching roles, leveraging creative methods, such as creative non-fiction, to amplify women`s voices.